A "Leaky" Pipeline and Chilly Climate in Archaeology in Canada. Issue 2 (April 2021) - Overholtzer, Lisa; Jalbert, Catherine L.
Abstract : This article quantifies the rate at which women archaeologists are present and retained in university departments. Drawing on publicly available data, we examine gender representation in (1) doctorates earned between 2002–2003 and 2016–2017; (2) Social Sciences and Humanities Research Council (SSHRC) grant applications and awards at the doctoral to senior levels between 2003 and 2017; (3) tenure-stream faculty at Canadian universities in 2019; and (4) placement of Canadian PhDs in the United States. These data demonstrate that women today represent two-thirds of all Canadian doctorates in archaeology, but only one-third of Canadian tenure-stream faculty, although not all archaeologists choose an academic career. In the last 15 years, women with Canadian PhDs have been hired into tenure-track positions in Canada at rates statistically lower than men, but at higher rates in the United States. Women apply for SSHRC archaeology grants in equal proportion to their presence, but men are awarded at a slightly higher rate. We end by discussing the possible reasons for this gendered attrition, including a "chilly climate"—that is, subtle practices that stereotype, exclude, and devalue women, as well as inhospitable working environments, particularly for primary caregivers. We warn that the current COVID-19 pandemic is likely to exacerbate these existing inequalities.